SOCIAL ASPECTS OF COOPERATIVE VALUES OF SOME TYPES OF COOPERATIVES IN BULGARIA - Georgi ALEKSIEV; Nadka KOSTADINOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
From their inception until now – the last 80 years – cooperatives are organizations that unite and balance the social and economic demands of society with the expectations of their members. Cooperative values and principles have been preserved for almost two centuries, which is proof of their sustainability and permanence. These values impress upon the societal values of freedom, equality and democracy. The aim of the present study is to study the social aspects of cooperative values in some types of cooperatives in Bulgaria. To achieve the goal, the following tasks are solved: (a) to examine the nature and character of cooperative values; and (b) to reveal the social aspects of these values by following their manifestation in individual Bulgarian cooperatives. To achieve the goal and solve the tasks, the methods of analysis and synthesis, induction and deduction, the structural-functional approach are applied. The main result of the study is that meeting the social needs of the member-cooperators in Bulgarian cooperatives occupies an important place, and for a significant part of the cooperators - a priority. From the analysis in this research, we can conclude that the social aspects of cooperative values in Bulgarian cooperatives makes them unique as a legal-organizational form, since these values are close to universal human values.